The Migration Dynamics of the Slovenian Territory in Historical Perspective - Lukšič-Hacin, Marina (Two Homelands, 2018)
The author presents an overview of the complex migration dynamics in Slovenia and its border regions over the last two hundred years. She covers migrations in “Austrian times”, during the First World War and the time of the first Yugoslavia, during the Second World War and the second Yugoslavia, and during the war in Yugoslavia and Slovenia’s gaining of independence. Both the intensive migration dynamics that occurred due to people’s seeking of employment and refuge, and the political movement of the borders, have been construed in migration studies as highly complex phenomena. This poses numerous challenges for interpreting how to understand migrations in 21st-century migration studies.